HEALTH INFORMATION MANAGEMENT (HIM) IN THE CONTROL OF MEDICAL CLAIMS ERRORS - Alshaban, Kashef K.; Almasri, Lina (International Journal of Research -GRANTHAALAYAH, 2020)
Preparing and submitting medical claims to health care providers is a crucial component in hospital finance. Owing to the complexity of the process, medical claims errors may result in financial issues. Our objective is to examine the process of preparing and submitting medical claims in the distinguished Healthpoint Hospital/Abu Dhabi, also the reasons for rejection of medical claims so as to focus in control hospital’s medical claims errors. The cases of claim rejection between the years 2014-2018 according to the hospital records are as follows: 2018 (January – May) 5%, 2017 4.4%, 2016 8%, 2015 & 2014 24%. Other cases of medical claims regarding Vitiligo (37 cases), obesity (14 cases), and Audiometry (23 cases) are also reviewed. It seems that the most common medical billing errors are related to technical and nontechnical errors. The strategy of controlling medical claims errors is designed in the hospital by applying key performance indicators (KPI) that demonstrate how effectively the hospital is achieving the key business objectives. The result proves that the strongest electronic system and applying the new business strategies led to reducing the rejections of medical claims due to mistakes.